Representasi Wanita dan Kesetaraan Gender dalam Novel ‘Dikta dan Hukum’ karya marah roesli: Sebuah Kajian Feminisme yang Holistik dan Sistematis” - Nensilianti; Ridwan; ra, St Zhafira (Jurnal Studi Gender dan Anak, 2026)
“Representation of Women and Gender Equality in Marah Rusli’s Novel ‘Dikta dan Hukum’: A Holistic and Systematic Feminist Study”This study examines the representation of women and gender equality in Marah Rusli’s novel “Dikta dan Hukum” through a holistic and systematic feminist approach. The novel, written in 1927, is a classic of Indonesian literature that portrays the lives of women in a patriarchal society. Using a feminist literary criticism framework, this study analyzes the female characters, their roles, and the power dynamics that shape their experiences. The findings show that the novel represents women as strong and independent individuals who struggle against patriarchal norms and social expectations. However, the novel also reinforces some patriarchal values, highlighting the complexity of gender relations in the context of the novel. This study argues that a holistic and systematic feminist approach is necessary to understand the nuances of gender representation in literary works, particularly in the context of Indonesian literature. The study concludes that “Dikta dan Hukum” offers valuable insights into the historical and cultural context of women’s experiences in Indonesia and contributes to the ongoing discourse on gender equality